2021
DOI: 10.2196/27015
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Emotional Burnout Regulation During the COVID-19 Pandemic: Multilevel Approach

Abstract: Background In February 2020, the Chinese government imposed a complete lockdown of Wuhan and other cities in Hubei Province to contain a spike of COVID-19 cases. Although such measures are effective in preventing the spread of the virus, medical professionals strongly voiced a caveat concerning the pandemic emotional burnout at the individual level. Although the lockdown limited individuals’ interpersonal communication with people in their social networks, it is common that individuals turn to soci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…The results corroborate a study that identified that heterosexual men had higher levels of emotional suppression [ 34 ]. This relationship is partially due to how men are socialized not to express their emotions in order to meet expectations and social rules related to a strong internalized male ideology [ 34 ]. Such ideology can operate through a set of cognitive factors that restrict emotional expressiveness, especially in contexts involving other people.…”
Section: Discussionsupporting
confidence: 88%
“…The results corroborate a study that identified that heterosexual men had higher levels of emotional suppression [ 34 ]. This relationship is partially due to how men are socialized not to express their emotions in order to meet expectations and social rules related to a strong internalized male ideology [ 34 ]. Such ideology can operate through a set of cognitive factors that restrict emotional expressiveness, especially in contexts involving other people.…”
Section: Discussionsupporting
confidence: 88%
“…In the case of the pandemic, the line between fear and anxiety will become less strong. Fear is related to a known or impending threat, whereas anxiety is mainly related to an imprecise or unknown threat [ 39 ]. So, the line will be created by the amount of knowledge that scientists, doctors, policy makers, media, or educators transmit about the virus.…”
Section: Discussionmentioning
confidence: 99%
“…From the initial case of the new coronavirus reported in China in December 2019, the virus spread rapidly on a global scale. The Chinese Government’s complete shutdown of all cities in the Hubei province, where the virus was first detected, in an attempt to halt the spread of the virus could not prevent its global impact [ 1 , 2 ]. China’s close relationship with other world countries in the field of trade and business paved the way for the virus to quickly spread to other countries.…”
Section: Introductionmentioning
confidence: 99%